PENGARUHÃÂ LATARÃÂ BELAKANGÃÂ ORANGÃÂ TUAÃÂ SEBAGAIÃÂ GURUÃÂ ÃÂ TERHADAPÃÂ MINATÃÂ MENGAJARÃÂ PADAÃÂ MAHASISWAÃÂ ÃÂ - FajarÃƒÂ‚Ã‚Â K, AndyÃƒÂ‚Ã‚Â ÃƒÂ‚Ã‚Â Rudiyanto; KarsonoÃƒÂ‚Ã‚Â , -; YudionoÃƒÂ‚Ã‚Â , Heri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2008)
PenelitianÃÂ iniÃÂ mengungkapkanÃÂ permasalahanÃÂ pengaruhÃÂ latarÃÂ belakangÃÂ orangÃÂ tuaÃÂ sebagaiÃÂ guruÃÂ terhadapÃÂ minatÃÂ mengajarÃÂ padaÃÂ mahasiswaÃÂ ProgramÃÂ StudiÃÂ PendidikanÃÂ TeknikÃÂ MesinÃÂ UniversitasÃÂ NegeriÃÂ SemarangÃÂ angkatanÃÂ 2007ÃÂ danÃÂ 2008.ÃÂ BerdasarkanÃÂ hasilÃÂ penelitianÃÂ dapatÃÂ disimpulkanÃÂ bahwaÃÂ latarÃÂ belakangÃÂ orangÃÂ tuaÃÂ sebagaiÃÂ guruÃÂ mempengaruhiÃÂ minatÃÂ mengajarÃÂ mahasiswaÃÂ sebesarÃÂ 38,24%.ÃÂ TetapiÃÂ variabelÃÂ latarÃÂ belakangÃÂ orangÃÂ tuaÃÂ sebagaiÃÂ guruÃÂ bukanÃÂ merupakanÃÂ satuÃ¢â¬ÂsatunyaÃÂ faktorÃÂ yangÃÂ mempengaruhiÃÂ minatÃÂ mengajarÃÂ padaÃÂ mahasiswa. KataÃÂ kunciÃÂ :ÃÂ LatarÃÂ BelakangÃÂ OrangÃÂ TuaÃÂ SebagaiÃÂ Guru,ÃÂ MinatÃÂ MengajarÃÂ ThisÃÂ researchÃÂ revealsÃÂ theÃÂ problemÃÂ inÃÂ whichÃÂ theÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacherÃÂ affectsÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ teaching.ÃÂ TheÃÂ studentsÃÂ wereÃÂ fromÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ programÃÂ SemarangÃÂ StateÃÂ UniversityÃÂ yearÃÂ 2007ÃÂ andÃÂ 2008.ÃÂ AccordingÃÂ toÃÂ theÃÂ resultÃÂ ofÃÂ theÃÂ research,ÃÂ theÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacherÃÂ affectsÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ teachingÃÂ aboutÃÂ 38,24%.ÃÂ However,ÃÂ thisÃÂ factorÃÂ isÃÂ notÃÂ theÃÂ onlyÃÂ factorÃÂ affectingÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ teaching.ÃÂ ItÃÂ isÃÂ justÃÂ oneÃÂ ofÃÂ manyÃÂ factors. ÃÂ Keywords:ÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacher,ÃÂ teachingÃÂ interest